Neg-raising believe and Maximize Presupposition - Alxatib, Sam; Ðurović, Ivana (Proceedings of the Amsterdam Colloquium, 2019)
We point out a puzzle that comes from the interaction of Maximize Presupposition (MP) with the Neg-raising verb believe. In response, we offer a reformulation of MP that we call Maximize Update (MU). MU compares not only the presuppositions of the relevant com peting forms, but the conjunctions of the forms’ presuppositions with their assertions. The principle favors the stronger of these. We compare MU with the possibility of combining MP with other accounts of neg-raising.